Population structure and phylogeography in Nassau grouper (Epinephelus striatus), a mass-aggregating marine fish. - Alexis M Jackson; Brice X Semmens; Yvonne Sadovy de Mitcheson; Richard S Nemeth; Scott A Heppell; Phillippe G Bush; Alfonso Aguilar-Perera; John A B Claydon; Marta C Calosso; Kathleen S Sealey; Michelle T Schärer; Giacomo Bernardi (PLoS ONE, 2014)
To address patterns of genetic connectivity in a mass-aggregating marine fish, we analyzed genetic variation in mitochondrial DNA (mtDNA), microsatellites, and single nucleotide polymorphisms (SNPs) for Nassau grouper (Epinephelus striatus). We expected Nassau grouper to exhibit genetic differentiation among its subpopulations due to its reproductive behavior and retentive oceanographic conditions experienced across the Caribbean basin. All samples were genotyped for two mitochondrial markers and 9 microsatellite loci, and a subset of samples were genotyped for 4,234 SNPs. We found evidence of genetic differentiation in a Caribbean-wide study of this mass-aggregating marine fish using mtDNA (FST = 0.206, p<0.001), microsatellites (FST = 0.002, p = 0.004) and SNPs (FST = 0.002, p = 0.014), and identified three potential barriers to larval dispersal. Genetically isolated regions identified in our work mirror those seen for other invertebrate and fish species in the Caribbean basin. Oceanographic regimes in the Caribbean may largely explain patterns of genetic differentiation among Nassau grouper subpopulations. Regional patterns observed warrant standardization of fisheries management and conservation initiatives among countries within genetically isolated regions.